Network-Based H∞ Control for Descriptor Systems With Time Delays Under a Novel Event-Triggered Strategy - Zhi, Ya-Li; Liu, Xu; Wang, Ying; Fan, Yuan (IEEE transactions on control of network systems, 2025)
This article focuses on the event-triggered H∞ control problem of the networked descriptor system with time delays. First, a novel event-triggered communication strategy is proposed, which can adaptively adjust the triggering parameters in light of dynamic errors. The expected control performance can be ensured in parallel with saving limited communication resources. Second, an integrated system model is established by considering network-induced delays, event-triggered strategy, and systems' time-varying delays. A co-design control method based on the event-triggered strategy is proposed by implementing the Lyapunov method. Finally, the effectiveness and advantages of the proposed method are presented through two examples.